Pengaruh Komitmen Organisasi, Motivasi, dan Pengalaman Kerja Terhadap Prestasi Kerja Karyawan (Studi pada PT. Kusuma Hadi Santosa, Karanganyar) - Ratriati, Putri Amanda; , Basworo Dibyo S.E,, M.Si (2016)
This study aimed to analyze the influence of leadership style, organizational culture and motivation on employee performance on PT. Kusuma Hadi Santosa, Karanganyar. This type of research is quantitative, the population of all employees PT. Kusuma Hadi Santosa and sampling using random cluster sampling technique or a simple random. Research data collection techniques through a questionnaire with a scale linker. Based on the results of multiple regression analysis obtained formulations Y = -7.068 + 0.974 x1 + 0.349 x2 + 0.370 x3 + e. where Y is the variable of job performance of employees, X1 is a organizational commitment, X2 is motivation and X3 is the job experience, the three constants of each variable is positive so that said positive influence on employee performance. The t-test studies show variable organizational commitment, motivation and job experience have a significant positive influence on employee performance. F test results can be analyzed that the three independent variables significantly influence employee performance, where the calculated F value of 78.059 and 0.000 significance level of <0.05. Last test research is a test of determination with R2 values of 0.715, meaning the independent variables have contributed to the variable performance of employees amounted to 71.5%, the rest is explained by other variables outside the model.